Les avant-gardes françaises de l’entre-deux-guerres face aux civilisations extra-occidentales - Guillaume Bridet (Itinéraires, 2009)
Members of the French avant-garde during the 20s and the 30s are not the first writers to be keen on extra-occidental civilisations. But they are the first ones to link this interest to a deep hate for their own civilisation. Therefore they hope that extra-occidental civilisations can provide a solution to Occidental aesthetic and political failure—which appears to be an illusion in the violent context of growing nationalisms.